A Randomized Controlled Trial Evaluating the See, Tilt, Align, and Rotate (STAR) Maneuver on Skill Acquisition for Simulated Ultrasound‐Guided Interventional Procedures. (1st June 2015) - Lam, Nicholas C. K.; Fishburn, Steven J.; Hammer, Angie R.; Petersen, Timothy R.; Gerstein, Neal S.; Mariano, Edward R.
Abstract : Objectives: Achieving the best view of the needle and target anatomy when performing ultrasound‐guided interventional procedures requires technical skill, which novices may find difficult to learn. We hypothesized that teaching novice performers to use 4 sequential steps (see, tilt, align, and rotate [STAR] method) to identify the needle under ultrasound guidance is more efficient than training with the commonly described probe movements of align, rotate, and tilt (ART). Methods: This study compared 2 instructional methods for transducer manipulation including alignment of a probe and needle by novices during a simulated ultrasound‐guided nerve block. Right‐handed volunteers between the ages of 18 and 55 years who had no previous ultrasound experience were recruited and randomized to 1 of 2 groups; one group was trained to troubleshoot misalignment with the ART method, and the other was trained with the new STAR maneuver. Participants performed the task, consisting of directing a needle in plane to 3 targets in a standardized gelatin phantom 3 times. The performance assessor and data analyst were blinded to group assignment. Results: Thirty‐five participants were recruited. The STAR group was able to complete the task more quickly ( P < .001) and visualized the needle in a greater proportion of the procedure time ( P = .004) compared to the ART group. All STAR participants were able to complete the task, whereas 41% of ART participants abandoned the task ( P = .003). Conclusions: Novices are able to complete a simulated ultrasound‐guided nerve block more quickly and efficiently when trained with the 4‐step STAR maneuver compared to the ART method.